A Novel Manual “Centrifuged-Enhanced” Cytosmear Technique for Improving Hypocellular Cytology in the Diagnosis of Vitreoretinal Lymphoma - Ho; Candice Ee Hua; Shen, Thaddeus Luke; Wang, Mona Meng; Wu, Meihui; Neo, Zhen Wei; Wee, Felicia; Yeong, Joe; Chan; Anita Sook Yee (Association for Research in Vision and Ophthalmology (ARVO), 2026)
Purpose
To develop a manual “centrifuged-enhanced cytosmear” technique for cytologic and immunohistochemical analysis of hypocellular vitreous biopsy specimens in vitreoretinal lymphoma (VRL).
Methods
Diffuse large B-cell lymphoma cells were diluted to simulate vitreous biopsy yields (1000–50,000 cells/100 µL) and fixed in PreservCyt. Samples were centrifuged in a standard laboratory centrifuge and deposited into 1000 cells/100 µL PAP pen–defined circles on charged slides. Smears were air-dried, methanol-fixed, and stained with toluidine blue and CD20 immunohistochemistry (IHC). Cell density per high-power field (40×) was quantified and compared with noncentrifuged smears. Reproducibility was assessed across replicates and between two operators. Genomic DNA concentration was measured.
Results
Centrifuged-enhanced cytosmears demonstrated significantly higher cellular densities than standard smears across all concentrations (P < 0.05), especially at 1000 to 2000 cells/100 µL, where standard smears failed to detect cells. CD20 IHC was successful without cell dropout. Genomic DNA yields ranged from 5.25 ng (1000 cells) to 143 ng (50,000 cells). Interuser variability was not significant. Comparison with cytospin clinical cases showed that centrifuged-enhanced cytosmears are of comparable cellularity to clinical cases.
Conclusions
This centrifuged-enhanced cytosmear technique reliably concentrates sparse cells for cytology and IHC. It is reproducible and cost-effective, requiring no specialized equipment. Genomic DNA yields at very low cell counts of 1000 cells/100 µL is potentially sufficient for adjuvant MYD88 mutation analysis and can be used to support cytology diagnosis.
Translational Relevance
​​​​​​​The centrifuged-enhanced cytosmear offers an accessible alternative to cytospin preparations, enabling VRL diagnosis and IHC analysis in settings lacking cytology infrastructure or where cell blocks cannot be performed.